Penguatan Komunikasi Lintas Budaya pada Siswa Tingkat Pertama Al-Hidayah Waqaf Foundation for Education and Social Development, Thailand - Muwahidah Nurhasanah; Hesvy Diniarty; Abdul Jabar Idharudin (BALE LITERASI, 2026)
This article discusses the implementation experience of the International Student Community Engagement Program (KKN Internasional) in Hatyai, Thailand, focusing on strengthening students' cross-cultural communication skills. The program serves as a real-world learning platform for students to apply their academic capabilities while adapting to distinct social and cultural contexts. The activities carried out included teaching Arabic and Indonesian at the TPQ Al-Hidayah Waqaf Foundation, participating in halaqah (religious study groups) with local women, and engaging in international seminars. This study employs a descriptive qualitative method with a case study approach. Data were collected through direct observation, documentation, and informal interviews with local residents to gain an in-depth understanding of the intercultural communication dynamics during the program. The primary objective of this community engagement project is to identify the cross-cultural communication challenges faced by students and to explain the adaptive strategies they utilized when interacting with the local community. The findings indicate that language and cultural differences posed the main obstacles in the communication process. However, students successfully overcome them through adaptive communication strategies, such as using visual media, learning basic Thai vocabulary, and employing non-verbal communication. These strategies proved effective in building harmonious and productive social relationships. Consequently, this initiative not only enhances students' cross-cultural communication skills but also strengthens Indonesian cultural diplomacy at the international level and opens up opportunities for cross-border academic collaboration. These findings underscore the importance of equipping students with cultural competence and foreign language skills prior to participating in international community engagement programs to ensure optimal adaptation and intercultural interaction.